Faktor-faktor yang Berhubungan dengan Risiko Kecelakaan Lalu lintas pada Siswa SMA di Kota Kupang Tahun 2019 - Dea Putrisna Djawa Gigy; Agus Setyobudi; Deviarbi Sakke Tira (Universitas Nusa Cendana, 2019)
The development of increasingly modern times with increasingly dense mobilization rates causes traffic accidents to increase, especially among high school students. Traffic accidents occur due to several factors, that are human factors, environmental factors, and vehicle factors. This study aimed to analyze factors related to the risk of traffic accidents in, Kupang city in 2019. This research used quantitative methods, with analytic methods, using a cross-sectional approach. The selection of samples used simple random sampling method and sample in this study is 84 students spread over three high schools, in Kupang. The results showed that there was a relationship between driving behavior with traffic accidents on high school students in Kupang with the value of p value = 0.003, there was no relationship between the factors of vehicles with traffic accidents on high school students in Kupang with the value of p value = 0.285 and there was a relationship between environmental factors and traffic accidents on high school students in Kupang with a value of p value = 0.002). The researcher proposes suggestions for high school students in Kupang City to pay more attention to driving behavior, as well as the conditions of the road being traversed. for officers who are authorized to be able to improve guidance and outreach, and strict rules and sanctions to create a conducive traffic situation, to reduce traffic accidents.